Non epileptic attack disorder, Psychiatric co morbidities and their outcomes: NEAD & Psychiatric Comorbidity - Sawant, Neena; Umate, Maithili (Nepal Journal of Neuroscience, 2022)
Background: NEAD is a common presentation in epilepsy clinics and is often misdiagnosed. This study was therefore planned to understand the prevalence of psychiatric co morbidities in patients diagnosed as NEAD and to study the outcome of both the conditions over 6 months with pharmacotherapy and supportive psychotherapy. Material & Method: 71 patients of NEAD were enrolled and assessed on SCID 1 to diagnose psychiatric co morbidity with rating of severity of anxiety & depression on HDRS & HARS. Patients were divided into Groups A & B depending on the presence or absence of existing co-morbid psychopathology respectively and were followed up over 6 months to assess outcomes. Psychiatric medication was given to Group A patients and both groups received supportive psychotherapy on follow up. Results: Group A had 50 patients with psychiatric co morbidity and Group B included 21 patients. Depressive disorders were common psychopathology and follow up at 3& 6 months revealed a reduction in the total mean scores of HARS and HDRS from baseline. Outcome of NEAD at the end of 6 months revealed 100% reduction in 28% and 50% reduction in 15 – 16% of both group patients. Conclusions: There are very few Indian studies on short or long term outcomes of NEAD and there is a need to create awareness among the treating physicians regarding the impact of associated psychiatric co morbidities which would affect the prognosis of NEAD.